Evaluation of Healthcare Outcomes of Patients Treated with 3D-Printed-Titanium and PEEK Cages During Fusion Procedures in the Lumbar Spine - Corso KA; Teferra AA; Michielli A; Corrado K; Marcini A; Lotito M; Smith C; Costa M; Ruppenkamp J; Wallace A (Medical Devices: Evidence and Research)
Katherine A Corso,1 Andreas A Teferra,1 Annalisa Michielli,2 Kristin Corrado,2 Amy Marcini,3 Mark Lotito,2 Caroline Smith,4 Michelle Costa,4 Jill Ruppenkamp,1 Anna Wallace1 1MedTech Epidemiology and Real-World Data Science, Johnson & Johnson, Raynham, Massachusetts & New Brunswick, New Jersey, USA; 2Clinical Research, DePuy Synthes, MedTech, Johnson & Johnson, Raynham, Massachusetts, USA; 3Medical Affairs, DePuy Synthes, MedTech, Johnson & Johnson, Raynham, Massachusetts, USA; 4Franchise HEMA, DePuy Synthes, Medtech, Johnson & Johnson, Raynham, Massachusetts, USACorrespondence: Katherine A Corso, MedTech Epidemiology and Real-world Data Science, Johnson & Johnson, 325 Paramount Drive, Raynham, MA, 02767, USA, Tel +1 857-523-0279, Email kcorso1@its.jnj.comPurpose: The objective of this observational, real-world study was to describe reoperation, revision, index healthcare utilization and hospital costs among patients treated with PEEK (polyetheretherketone) or 3D-printed-titanium cages during lumbar/lumbosacral posterior fusion procedures, either TLIF (transforaminal lumbar interbody fusion) or PLIF (posterior lumbar interbody fusion). Statistical comparisons were not conducted.Methods: This was a descriptive, retrospective, observational study. Patients with PEEK (OPAL™, DePuy Synthes, Raynham, MA) or 3D-printed-titanium (CONDUIT™ TLIF (transforaminal lumbar interbody fusion)/PLIF (posterior lumbar interbody fusion) Cage/EIT™ Cellular Titanium TLIF/PLIF Cage (DePuy Synthes, Raynham, MA)) spinal cages were identified in the Premier Healthcare Database between 1/1/2007 and 9/30/2022. Patients were required to have posterior approaches of the lumbar/lumbosacral spine and DDD, stenosis, back pain, instability, spondylolisthesis, or pseudarthrosis/failed prior surgery. Patient and procedure, healthcare utilization and hospital cost data were collected at the index surgery, and patients were followed up to 3 months for reoperation and 12 months for revision. All data were summarized descriptively, and no statistical comparisons were made between cage groups.Results: A total of 5118 PEEK and 1189 3D-printed-titanium cage patients were included in this study. Among 3D-printed-titanium cages, 804 had PLIF and 345 had Curved TLIF cage types. Most PEEK cage patients were 18– 64 years (61.9%), and 3D-printed-titanium was evenly distributed across age categories. The mean index hospital cost was ~$40,000, LOS was ~3 days, and discharge status to home/home health was ~85% for both; surgery time was 267 minutes for PEEK and 280 minutes for 3D-printed-titanium. The 0– 3 month reoperation cumulative incidence was 1.0% for PEEK and 1.3% for 3D-printed-titanium. For revision, incidence within 0– 3, 4– 6, and 7– 12 months was 1.2%, 0.6%, and 1.7% for PEEK and 1.6%, 0.5%, and 1.2% for 3D-printed-titanium. The mean costs per patient associated with reoperation and revision for the entire cohort were $220 and $1228 for PEEK and $290 and $1754 for 3D-printed-titanium.Conclusion: This study provides real-world economic insights into an area where practice data are sparse, within hospital settings for PEEK and 3D-printed-titanium spinal cages. A key study limitation is the descriptive design in which potential confounding factors that may affect the outcome estimates are not addressed.Keywords: spinal cage, 3D-printed, lumbar fusion, reoperation, revision rates, healthcare utilization, real-world data